„Nie doniosły na mężów – poniosły karę”, czyli kilka uwag o książce "Bez winy i bezprzyszłości. Losy członków rodzin „zdrajców ojczyzny” represjonowanych na mocy rozkazu NKWD nr 00486" - Olechowski, Piotr (1990– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
The review article critically analyses the monograph published by the Institute of National Remembrance Publishing House in early 2024. The book in question refers to the fate of victims sentenced under order no. 00486, addressed primarily to women: wives of “enemies of the people”, whose only “guilt” was that they had not denounced their husbands to the state security organs. The text not only analyses the book content but also points out several substantive errors, incorrectly used nomenclature, and an inadequate, at times, selection of source material.
p. 205-224
Concerns book: Bez winy i bez przyszłości : losy członków rodzin "zdrajców ojczyzny" represjonowanych na mocy rozkazu NKWD nr 00486 / Iwan Kozłowski, Mariusz Kwaśniak, Bożena Witowicz, Paweł Zielony ; Instytut Pamięci Narodowej - Komisja Ścigania Zbrodni przeciwko Narodowi Polskiemu. - Warszawa : Instytut Pamięci Narodowej Komisja Ścigania Zbrodni przeciwko Narodowi Polskiemu, 2024.
Summary in English and Russian.
Keywords: historiography; repressions; Poles in the USSR; Great Terror; order no. 00486; Ukraine; women; Soviet Union. Narodnyĭ komissariat vnutrennikh del - and Poland; women political prisoners - Soviet Union; Polish people - government policy - Soviet Union - history; Polish people - persecution - Soviet Union; Polish people - Soviet Union - 1900-1945; Polish people - Ukraine - 1900-1945